Documentary Sources of School Historical Education in Subcarpathian Rus - Kovach, Artur (Pedagogical Discourse, 2013)
The article is dedicated to documentary sources of school historical education issued in the period from 1919 till 1938 on the territory of Subcarpathian Rus. Author analyses legal acts, documents of clerical work, statistics, reference materials, procedural guideline materials, pedagogical printed press, journalism and personal documents, which show condition of historical education at schools. Review the source base is made in the light of French and Russian scientific traditions that distinguish the two categories of documents: «source» and «literature». Therefore, from documentary sources we isolated only original materials related to the period of the 1920s and 1930s., or created by contemporaries of that period.